Phytotherapeutic approaches to treatment and prophylaxis in pediatric practice - Valentina Petkova; Bozhidarka Hadzhieva; Paraskev Nedialkov (Pensoft Publishers, 2019)
Medicinal plants, their extracts and herbal medicinal products occupy a growing share of medicines in the pharmacy worldwide. Historically, the first medicines were products of plants, as well as some of the most important medicines still in use today. With the development of phytochemistry, as part of the pharmaceutical science, great progress has been made in the isolation and in determining the value of a number of biologically active substances (BAS). Many plants have yielded pure substances (or natural products) that are applied in modern medical practice. Other compounds are potentially useful or have toxic effects. Traditional medicine incorporating many herbal medicines remains an important (and in some cases, the only) form of treatment in some countries, with increasing use in medical practice. On the other hand, the fact that in pediatric patients there is a limitation, mainly moral and ethical, of the number of medications to be administered due to the difficulty of conducting clinical trials in children, stimulates the use of herbal medicines of proven quality, effectiveness and safety among this group of patients.